“Mosaic Pattern” Foreign Bodies in Computed Tomography of the Head: A Specific Sign to Detect Tempered Glass-Related Head Injury - Mohd. Faheem; Raj Kumar; Manish Jaiswal; Mohammad Ahmed Ansari; Noor us Saba (Indian Journal of Neurosurgery)
A 40-year-old male patient presented to us with a history of road traffic accident, followed by loss of consciousness and vomiting. Noncontrast computed tomography (NCCT) scan revealed frontal bone defect along with multiple “mosaic pattern” homogenously hyperdense foreign bodies of nearly similar size in the right frontoparietal region within the extradural space. Debridement craniectomy was done, and multiple pieces of glass were retrieved. The extremely unique radiologic finding and probably first in the English literature prompted us to report this interesting case. Unfortunately, the patient died of myocardial infarction 3 days after the injury. Further, this new “mosaic pattern” radiologic finding on NCCT of the head may help in determining the mechanism of injury due to tempered glass-related head trauma. Window glass may not be always safe as it is thought by commuters.